Fitotelmata fauna on the bromeleans Aechmea fendleri André y Hohenbergia stellata Schult of the San Esteban Nacional Park, Venezuela - Liria, Jonathan (2007)
In the present work, we characterize the associations of mosquitoes species and other inverte- brates on bromeliads from San Esteban National Park in Carabobo State, Venezuela. Eighteen plants of Aechmea fendleri (11) and Aechmea fendleri (1 1) and Aechmea fendleri Hohenbergia stellata (7) were sampled in rainy (September 2004) and dry (March 2005) seasons. A total of 2020 macroinvertebrates were collected. The most important was the Diptera Order, with the Families Chironomidae (43%), Chaoboridae (25%) and Culicidae (6%), and the Coleoptera, Scyrtidae (5%). In Culicidae the most abundant species were Culex consolator (31%), Culex consolator (31%), Culex consolator Cx. neglectus (27%) and Wyeomyia celaenocephala (17%). The highest abundance and richness was in dry season, when Culicidae diversity increases. The diversity and evenness was similar among season and it was highest in H. stellata .